ANTIVIRUS PERFORMANCE EVALUATION AGAINST POWERSHELL OBFUSCATED MALWARE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In recent years, malware attacks have become increasingly sophisticated, and the methods used by attackers to evade Windows defenses have grown more complex. As a result, detecting and defending against these attacks has become an ever more pressing challenge for security professionals. Despite significant efforts to improve Windows security, attackers continue to find new ways to bypass these defenses and infiltrate systems. The techniques covered in this paper are all currently active and effective at evading Windows defenses. Our findings underscore the need for continued vigilance and the importance of staying up to date with the latest threats and countermeasures.